Economics of advanced technologies for wastewater treatment: Evidence from pulp and paper industry - Dagar, Sumit; Singh, Santosh Kumar; Gupta, Manoj Kumar (Frontiers in Environmental Science, 2022)
Paper mills generate large quantities of wastewater and sludge waste depending on the type of paper making processes employed. This poses several problems regarding wastewater treatment, discharge, and sludge disposal. Whenever wastewater is generated, it should be treated in wastewater treatment plants prior to being released to the environment since it can be polluting and dangerous. A study was conducted at Star Paper Mills Ltd. Saharanpur, UP to demonstrate the existing and advanced technologies for wastewater treatment. The mill uses woody raw materials such as eucalyptus, poplar, and veener chips to manufacture a wide range of industrial and cultural grade papers, such as absorbent kraft, maplitho, azure lay, and copier. We observed that the most common excess back water is from paper machines, bleach plant effluent, floor cleaning, and other sources of wastewater. High chemical oxygen demand (COD), biochemical oxygen demand (BOD), and low biodegradability are all characteristics of pulp and paper wastewater. Approximately 85–90% of the fresh water utilized is wasted. We examined the wastewater collected and evaluated from the paper mill by Central Pulp & Paper Research Institute (CPPRI). The Effluent treatment plant (ETP) at Star Paper Mills Ltd. is sufficient to facilitate satisfactory removal of suspended matter in clarifiers and oxidation of biodegradable organic matter in aeration tank. As a matter of fact, if the ETP is operated under optimal conditions, the aeration capacity is sufficient to effectively treat even higher BOD loads than the existing load.